[Winnowing Rice Grain] - (:unkn) unknown (M. Jolly, Trinidad, 2009)
A picture of three people cleaning rice. A description on the back of the postcard reads "An almost Biblical scene common in Trinidad. The lady, aided by the constant trade winds, is winnowing the rice grain from the chaff."
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Rice; Rice--Drying